The Effect of Mindfulness-Based Cognitive Therapy on Anxiety and Depression Levels in Breast Cancer Patients: A Systematic Review - Norwinda Norwinda; Yulis Setiya Dewi; Ilya Krisnana (Indonesian Journal of Global Health Research, 2024)
Cancer is closely associated with several anxiety issues and depression is the most common comorbidity of cancer. It has been stated that 60% of individuals with cancer have psychological symptoms (depression and anxiety) related to cancer and according to the American Cancer Society, more than 25% of cancer patients suffer from symptoms of clinical depression. Methods: This study is a systematic review that analyzes 11 articles that are relevant to the topic, articles are searched through Pubmed, SpringerLink, Sciencedirect and Google Scholar from 2019-2023. Keywords used ((“Mindfulness Based Cognitive Therapy” OR “MBCT”) AND (“Anxiety” OR “Anxiety Disorders”) AND (“Depression” OR “Depressive Disorder”) AND (“Breast Cancer” OR “Breast Neoplasm” OR “Breast Carcinoma” OR “Breast Tumor'')).Results: The provision of mindfulness based cognitive therapy in 11 articles applied to various ages and to patients experiencing anxiety and depression in various countries with results showing effectiveness in preventing relapse and overcoming anxiety and depression by providing therapy for 8 weeks with a single administration for 90 minutes. Conclusion: The provision of mindfulness based cognitive therapy for 8 weeks with a single administration for 90 minutes can prevent and overcome anxiety and depression. Therefore, it is expected that nurses can apply this evidence based nursing as a preventive and curative effort.